Thyrotoxic Hypokalemic Periodic Paralysis: Pathophysiological Mechanisms - Gan Qing; Wan Nur Amalina Zakaria; Fatimah Zahra Mohamad Rom; Wan Nor Fazila Hafizan Wan Nik; Hani Ajrina Zulkeflee; Siti Nadirah Ab Rahim (Korean Endocrine Society, 2026)
Non-Indexed Publication